Analyzing Failed Institutional Change Attempts. (March 2022) - Issar, Sukriti; Dilling, Matthias
Theoretical advances in the study of institutional change center around a productive paradox. While change agents can take strategic action to change institutions, institutions display a remarkable level of formal stability. From this paradox, we expect that attempts to change institutions are an empirical regularity and that many formal change attempts will fail. This article contributes to historical institutionalism by analyzing the political effects of failed formal institutional change attempts on institutional sequences. Failed institutional change attempts could be mere blips, having little effect on subsequent institutional trajectories, or even inoculate against future attempts. Failed attempts could also lay the ideational groundwork, aid in coalition building, and garner concessions for subsequent institutional change, or convince change agents to alter their strategy. The article suggests analytical strategies to assess the effects of failed institutional change attempts, drawing on examples from comparative politics and two extended case illustrations from Italian party politics and the Affordable Care Act in the United States.